Adoptees facing adolescence: What accounts for their psychological well‐being?. (7th April 2021) - Ranieri, Sonia; Ferrari, Laura; Danioni, Francesca Vittoria; Canzi, Elena; Barni, Petra; Rosnati, Rosa; Rodriguez, Maite Roman
ABSTRACT: Introduction: In accordance with the "resilience paradigm", this study was aimed at exploring the role of the parent‐child relationship in supporting internationally adopted adolescents' ability to develop a strong adoptive identity and a feeling of satisfaction with their own life. Methods: Participants were 105 Italian adopted adolescents (13–17 years) asked to complete a self‐report questionnaire. Results: Results showed that adolescents generally feel fairly comfortable discussing adoption‐related issues (especially with their mothers), have a medium‐high level of adoptive identity, and appear to be quite satisfied with their life. Moreover, while adoptive identity mediates the association between openness in communication regarding adoption and adoptees' well‐being with mothers, father‐child communication openness has a direct influence on well‐being. Conclusions: Findings highlighted that the quality of mother‐child and father‐child relationship plays a crucial role in guiding the process of adoptees' identity formation and influencing their well‐being. Recommendations for professionals working with adoptive families were discussed.